Using carbon steel in the stripper and reboiler for post-Combustion CO2 capture with aqueous amine blends. (August 2016) - Yu, Louis C.Y.; Sedransk Campbell, Kyra L.; Williams, Daryl R.
Graphical abstract: Highlights: MEA + AEPZ generally show more corrosive behaviours on carbon steel than MDEA + AMP. Carbon steel corrosion in MEA + MDEA, MEA + AMP, AEPZ + MDEA and AEPZ + AMP blends. Increased concentration of 3° or SH amine to 1° or 2° amine precipitates more FeCO3 . Layers of FeCO3 form physical barrier, reducing Fe ion flux. Abstract: Aqueous amine solutions loaded with CO2 show a range of corrosion behaviour when in contact with carbon steels. Primary (1°) and secondary (2°) amines undergo corrosion, including the formation of iron oxide surface layers. By contrast, tertiary (3°) and sterically-hindered (SH) amines produce an excess of carbonate ions, leading to FeCO3 formation, and thereby reducing corrosion. Four amines were tested under challenging conditions (1–5 M at 120 °C) to confirm these behaviors. Due to recent interest in blended amine solvents (1° or 2° with 3° or SH) for improved reaction kinetics, CO2 absorption capacity and recoverability, four binary amine combinations (MEA + MDEA, MEA + AMP, AEPZ + MDEA, AEPZ + AMP) were tested in a range of compositions. Blends containing low concentrations of 1° or 2° amine show promise for use with carbon steel due to the formation of a siderite product layer and low corrosion levels. An increase in concentration of 1° or 2° amines, shows higher Fe ion concentrations initially as well as significant weight change to the coupon. However, the formation of more diverse product layers at longer time intervals reduces the Fe ion concentration in the bulk. Blends generally offer reduced corrosion compared to 1° or 2° amines alone, another benefit towards deployment.